2017
DOI: 10.3389/fnhum.2017.00309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of More-Affected vs. Less-Affected Motor Cortex tDCS in Parkinson’s Disease

Abstract: Objective: To evaluate therapeutic potential of different montages of transcranial direct current stimulation (tDCS) in Parkinson’s Disease (PD) patients with asymmetric motor symptoms.Materials and Methods: Fourteen patients with asymmetric PD underwent, while on treatment, seven separate sessions including electrophysiological and clinical evaluation at baseline and after anodal, cathodal and sham tDCS of the primary motor cortex (M1) of the two hemispheres. Changes in motor cortical excitability were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…and Coesntino et al . showed that treatment with tDCS produced significant improvements in UPDRS-III scores in humans 17 , 30 . Furthermore, tDCS also had beneficial effects on cognitive function and freezing of gait 31 .…”
Section: Discussionmentioning
confidence: 99%
“…and Coesntino et al . showed that treatment with tDCS produced significant improvements in UPDRS-III scores in humans 17 , 30 . Furthermore, tDCS also had beneficial effects on cognitive function and freezing of gait 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the results showed improved finger tapping rates when anodal tDCS was applied to the more affected M1 and when cathodal tDCS was applied to less affected M1, UPDRS part III scores was reduced after anodal tDCS was applied to the more affected M1, but did not change after cathodal tDCS was applied to the less affected M1. 116 Other studies combined tDCS with rehabilitation to treat gait disturbance in PD. One study showed improved gait and motor performance after tDCS to SMA combined with gait training.…”
Section: Clinical Effects Of Tdcs and Tacsmentioning
confidence: 99%
“…Cosentino and colleagues pointed to different effects of tDCS when targeting the M1 of the most-or less-affected hemisphere in PD. They found that only anodal tDCS applied to the most-affected hemisphere resulted in increased cortical excitability together with improved motor performance (Cosentino et al, 2017). Moreover, pairing tDCS to training of gait resulted in significantly greater benefit than the effects of tDCS and training as single therapy (Kaski et al, 2014).…”
Section: Effects Of Tdcs On Freezing Episodes and Non-freezing Writinmentioning
confidence: 99%
“…Several studies used tDCS as a single or adjuvant intervention in Parkinson rehabilitation (for reviews see Broeder et al, 2015;Elsner, Kugler, Pohl, & Mehrholz, 2016;Ferrucci, Mameli, Ruggiero, & Priori, 2016;Goodwill et al, 2017;Tahtis & Kaski, 2017). Improvements in upper limb performance of PD patients were found after anodal tDCS compared to sham when stimulation was applied to the primary motor cortex (M1) in rest (Benninger et al, 2010;Cosentino et al, 2017;Fregni et al, 2006) as well as during task performance (Salimpour, Mari, & Shadmehr, 2015). Moreover, changes in M1 excitability after repetitive TMS of the supplementary motor area (SMA) in rest were related to increased writing performance in PD (Randhawa, Farley, & Boyd, 2013).…”
Section: Introductionmentioning
confidence: 99%